Developing web-based EFL literacy resources: A highlight on literacy level - Aji Nurohman; Nana Priajana; Muhsiyana Nurul Aisyiyah (Fakultas Ilmu Tarbiyah dan Keguruan (FITK) UIN Siber Syekh Nurjati Cirebon, 2024)
Generally, Indonesian students need to improve their literacy. According to the 2022 PISA study results, 70% of Indonesian students are below the minimum literacy competency level. It shows Indonesia's standard student literacy level is still at level 2 PISA. Therefore, this study aims to develop EFL digital literacy resources that can assist learners in improving their literacy skills. This research is an research and development (R&D) study using the ADDIE method. The data was obtained from literature review analysis regarding website characteristics and MCA (Minimum Competency Assessment) literacy questions. The analysis results show there are eight characteristics of an excellent website for learning that should be considered when developing literacy resources, and MCA questions can be used to measure students' literacy levels. In the design and development stages, the website was developed based on the characteristics of a good website obtained in the analysis stage. Following the MCA model, the website contains fiction and nonfiction text that can foster creativity and critical thinking skills. By using interactive features and appealing visuals, a fun and educational literacy experience is created for students.Keywords: digital learning resources, literacy, MCA, reading resources,